Microbiological profile of slow-growing non-tuberculous mycobacteria species other than Mycobacterium avium complex - Fernandez-Pittol, Mariana; Batista, Sara; Narváez, Sofía; Román, Angely; San Nicolás, Lorena; Martínez, Diego; Oliver, Laura; González-Moreno, Olga; Martínez, José Antonio; García, Felipe; Amaro-Rodríguez, Rosanel; Soler, Néstor; et al. (Frontiers in Microbiology, 2025)
IntroductionMycobaterium avium complex (MAC) and Mycobacterium abscessus complex are the primary agents of non-tuberculous mycobacteria infection. However, other species within the slow-growing group can also be potentially pathogenic, although information on these species is limited.ObjectivesWe conducted a prospective analysis of slow-growing species other than MAC, aimed at the identification and microbiological profiles of clinical samples from a tertiary hospital. The Microbiology Department of the Hospital Clinic of Barcelona, the Microbiology Laboratory of SYNLAB Laboratories, and the Microbiology Laboratory of Hospital Sant Joan de Deu participated in the study.MethodsSpecies identification was conducted by MALDI-TOF MS and/or 16S rRNA and rpoB gene sequencing. Drug susceptibility tests (DST) were performed using the microdilution method. The results of the susceptibility profiles were compared with treatment guidelines, or the most recent literature related to each species.ResultsTwenty-five different species belonging to the slow-growing group were identified. The most frequently observed were M. xenopi, M. kansasii, M. gordonae, and M. marinum. In this series, M. lentiflavum presented the highest susceptibility profile, while M. simiae demonstrated the highest level of resistance. Clarithromycin, rifabutin, and amikacin demonstrated high levels of effectiveness across all species. The species most associated with infection, presented a high correlation with the clinical treatment guidelines.ConclusionA specific susceptibility profile was observed among all the species. The in vitro profiles of the most frequent species correlated with the clinical treatment guidelines, reinforcing the supporting role of DST in the design of individualized treatment for each patient.